2008
DOI: 10.4049/jimmunol.181.11.7449
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TheIdd3Genetic Interval Determines Regulatory T Cell Function through CD11b+CD11c− APC

Abstract: The Idd3 genetic interval confers protection against multiple autoimmune diseases, including type 1 diabetes and experimental autoimmune encephalomyelitis. The favored candidate gene in this interval is Il2, which is polymorphic between susceptible and resistant strains of mice. IL-2 regulates the growth/death of effector T cells as well as the generation/maintenance of regulatory T cells (Tregs), and recent studies have shown that NOD.Idd3 Tregs are more suppressive than their NOD counterparts. We have furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Given that NOD.Idd3 mice are protected from T1D and that both IL-2 and IL-21 can modulate the development of induced Tregs and Th17 cells, we assessed the balance of regulatory and pathogenic T cells in these mice. We and others have previously shown that the frequency of Tregs is not significantly different between NOD and diabetes-resistant NOD.Idd3 mice (8,9,23,24). However, in prediabetic mice, we found that the ratio of Tregs/Th17 cells was higher in NOD.Idd3 mice than in NOD mice in both the splenic and pancreatic draining LN compartments ( Figure 2).…”
Section: Figurementioning
confidence: 33%
See 4 more Smart Citations
“…Given that NOD.Idd3 mice are protected from T1D and that both IL-2 and IL-21 can modulate the development of induced Tregs and Th17 cells, we assessed the balance of regulatory and pathogenic T cells in these mice. We and others have previously shown that the frequency of Tregs is not significantly different between NOD and diabetes-resistant NOD.Idd3 mice (8,9,23,24). However, in prediabetic mice, we found that the ratio of Tregs/Th17 cells was higher in NOD.Idd3 mice than in NOD mice in both the splenic and pancreatic draining LN compartments ( Figure 2).…”
Section: Figurementioning
confidence: 33%
“…We showed previously that NOD-derived CD11b + APCs inhibit Treg function (9). We now present data that show that this same APC population also promotes Th17 cell differentiation in NOD mice relative to that of NOD.Idd3 congenic mice.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations